RELATIONSHIP BETWEEN FIRM CHARACTERISTICS AND DISCLOSURE LEVEL: A STUDY WITH SPECIAL REFERENCE TO NON-BANKING FINANCIAL COMPANIES IN INDIA - Kumar, Bidyut; Das, Sweety (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the impact of firm characteristics specifically firm size, firm age, and profitability on the level of financial disclosure among Non-Banking Financial Companies (NBFCs) in India. The objective is to assess how these factors influence disclosure level, measured through a disclosure index based on key items related to corporate governance, financial performance, and regulatory compliance. Data from 10 prominent NBFCs, including Bajaj Finance and HDFC Ltd etc., were collected from their Annual Reports for 2023. Multiple regression analysis was used to evaluate the effect of firm size, firm age, and profitability (measured by ROA and net profit margin) on the disclosure score. Descriptive statistics show wide variation in firm size (mean: ₹1134.70 crore), firm age (mean: 28.9 years), and ROA (mean: 3.63%). The disclosure score ranges from 0.46 to 0.82, with a mean of 0.67. Regression results indicate that firm size (β = 0.025, p < 0.05) and firm age (β = 0.015, p < 0.01) significantly positively influence disclosure, while ROA (β = 0.020, p < 0.05) shows a smaller impact. The net profit margin was not significant (p > 0.05). The model explains 72% of the variance in disclosure scores (R² = 0.72), highlighting the importance of these firm characteristics in promoting financial transparency among NBFCs.